Incidence, retrieval methods, and outcomes of intravascular ultrasound catheter stuck within an implanted stent: Systematic literature review. Issue 2 (February 2020) - Hiraya, Daigo; Sato, Akira; Hoshi, Tomoya; Sakai, Shunsuke; Watabe, Hiroaki; Ieda, Masaki
Highlights: Intravascular ultrasound (IVUS) catheter entraps in small diameter drug-eluting stent for tortuous and/or calcified lesions. Entrapped IVUS catheter could be retrieved using a variety of retrieval techniques. This is the first review investigating the IVUS catheter entrapment in detail. Interventional cardiologists should remember the percutaneous retrieval techniques. Abstract: Background: There have been no reviews regarding intravascular ultrasound (IVUS) catheter entrapment during percutaneous coronary intervention (PCI). This study investigated the incidence, retrieval methods, and outcomes of IVUS catheter stuck within implanted stents. Methods: Between January 2015 and July 2018, a total of 794 consecutive patients underwent PCI for coronary artery disease. Among them, 705 patients underwent stent implantation using IVUS. The patients with IVUS catheter entrapment in an implanted stent were investigated. Results: Ten patients (1.4%) suffered from an IVUS catheter stuck in an implanted stent. Among them, 7 patients had very tortuous lesions while 5 patients had severely calcified lesions. Seven patients (70%) underwent placement of the 3rd generation drug-eluting stent (DES), and the stent diameters were ≤2.5 mm among 8 patients (80%). Retrieval methods were the buddy wire technique, the double guide catheter technique, covering the exit port of IVUS catheter with a balloon catheter, and covering with GuideLiner® catheter (Vascular Solutions Inc., Minneapolis, MN, USA). On multivariable analysis, the predictors of IVUS catheter entrapment were tortuous lesion [odds ratio (OR), 8.21; 95% confidence interval (CI), 2.19–30.7; p = 0.002], 3rd generation DES (OR, 5.31; 95% CI, 1.08–26.1; p = 0.021), and stent diameter ≤2.5 mm (OR, 6.31; 95% CI, 1.29–30.8; p = 0.010). Furthermore, we identified 6 cases of IVUS catheter entrapment through a systematic literature review. Conclusions: The IVUS catheter was almost stuck in tortuous lesions and the 3rd generation DES with a small diameter. We could successfully retrieve it in all cases using various retrieval techniques.